INTEGRATED STRATEGY OF INNOVATIVE DEVELOPMENT OF AGRICULTURE - NISHCHAKOV, IHOR; KHOLODIUK, OLEKSANDR (Herald of Khmelnytskyi National University. Technical sciences, 2024)
Innovations are a key factor in the development of agriculture in Ukraine and globally. Globalization and the dynamics of the global economy require effective innovation strategies to ensure the competitiveness of Ukraine’s agricultural sector. The essence of innovations in agriculture is to improve production technologies, update the technical base, and increase the efficiency of each process. The literature review in this paper confirms the relevance of the topic of innovation in agriculture. This study uses qualitative and quantitative methods. The study uses the Scopus and Google Scholar databases to search, select and systematize literature sources, focusing on key terms. The selection criteria include relevance, topicality, scientific credibility, methodology and research approach, and citation. The study also includes a quantitative analysis of R&D expenditures in Ukraine with a focus on agriculture. The results of the analysis are presented in graphs. The conclusions present generalized development strategies, with a focus on the integration of information and digital technologies, co-development of innovations with environmental sustainability, financial support and cooperation between sectors of the economy.